(untitled) (International Seven Journal of Multidisciplinary, 2025)
The study analyzed corporate social responsibility practices in the Brazilian construction sector, identifying how social, environmental, and governance actions contribute to sustainable results and greater competitiveness. The research was carried out through a qualitative bibliographic review, considering publications from 2015 to 2024, with emphasis on real experiences of companies that implemented training programs, inclusion policies, waste management, and technological innovation. The findings showed that these practices generate economic gains, reduce environmental impacts, and strengthen ties with communities, enabling the creation of safe workplaces and the generation of shared value. It was found that the use of sustainable materials and the adoption of environmental certifications increase the credibility of construction companies, while transparency in reports and investment in social projects ensure investor confidence and social acceptance of projects. It is concluded that corporate social responsibility is an essential strategic pillar for companies seeking to stand out in a competitive market, integrating financial objectives with lasting collective benefits.